Associations of residual left ventricular and left atrial remodeling with clinical outcomes in patients after aortic valve replacement for severe aortic stenosis. Issue 3 (September 2016) - Hatani, Takeshi; Kitai, Takeshi; Murai, Ryosuke; Kim, Kitae; Ehara, Natsuhiko; Kobori, Atsushi; Kinoshita, Makoto; Kaji, Shuichiro; Tani, Tomoko; Sasaki, Yasuhiro; Yamane, Takafumi; Koyama, Tadaaki; et al.
Abstract: Background: Aortic valve replacement (AVR) is currently the standard therapy for severe aortic stenosis (AS), and regression of left ventricular (LV) hypertrophy after AVR has been reported. However, data regarding a temporal relation between LV mass and left atrial (LA) volume are limited, and their prognostic impacts have not been fully elucidated. We aimed to clarify the temporal patterns of LA and LV reverse remodeling and their associations with clinical outcomes. Methods: We retrospectively reviewed 198 consecutive patients who underwent AVR for severe AS. After excluding patients with prior cardiac surgery, atrial fibrillation, concomitant moderate to severe aortic regurgitation, or concurrent mitral valve surgery, 83 patients with echocardiographic LV mass index (LVMI) and LA volume index (LAVI) data before and 1 year after AVR were eligible for the outcome analysis and 29 patients with these 2 measures before surgery, 1 month, 1 year, and 3 years after surgery were eligible for the analysis of time-dependent change of LVMI and LAVI. Results: Significant reductions in LVMI and LAVI (both p < 0.001) after surgery were observed over time. LA dilatation improved and reached a plateau 1 month after surgery, whereas LV hypertrophy improved more gradually and reached a plateau at 1 year. The presence of both LV hypertrophy and LA dilatation 1 year after surgery was associated with significantly higher mortality (patients with both conditions vs. patients with neither or one condition = 22.6% vs. 7.3% at 3 years; p = 0.031) and major adverse cardiac and cerebrovascular events (38.9% vs. 12.6% at 3 years; p = 0.021). Conclusions: LA reverse remodeling occurred rapidly after AVR for severe AS, and regression of LV hypertrophy was more gradual. The presence of both residual LV hypertrophy and LA dilatation 1 year after AVR was associated with poor long-term outcomes.